Obtaining and properties of structurally-dyed alkyd resin - Тараненко, Наталья Николаевна (Technology audit and production reserves, 2014)
Dyed polymers are prepared by mixing a polymeric material and a dye. For uniform dyeing it is necessary to grind a dye. Some dyes have such properties as hydrophilicity and tendency of dyes to form agglomerates, which negatively affect the dyeing process, require additional equipment. The method of structural polymer dyeing can eliminate these difficulties. The aim of our research is to study regularities of producing structurally-dyed alkyd resin, modified by oil. The scheme of obtaining the structurally-dyed resin, modified by oil can be represented as follows. Firstly, the reesterification of pentaerythritol by oil is carried out. At the second stage, azopigment is added to interesterificator. Then, we add the phthalic anhydride and glycerol and conduct the polycondensation up to the specified acid number. The possibility of obtaining structurally-dyed alkyd resin, modified by oil was shown. Structurally-dyed alkyd resin has high pigment properties and can be used as an oligomeric dye.